Sosialisasi Penguatan Karakter Sopan dan Santun Melalui Sikap Bahasa Positif pada Karang Taruna RT.001/RW.004 Tanah Baru, Beji, Kota Depok, Jawa Barat - Ila Nafilah; Reni, Reni Rokhayati; Yulia, Yulia Agustin; Eko, Eko Yulianto (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Character in the sense of attitude or behavior is closely related to language, and this relationship is logical or structural because language is a reflection of a person's attitudes and behavior.  Language is a symbol of human existence that can be known about their desires, educational background, customs, even their region or country of origin.  When someone communicates by choosing polite words and expressions, that person will use good sentences. Providing direction and socialization about positive language attitudes can improve language skills and foster polite and polite character among teenagers. This community service activity was held at youth youth organization Rt.001/Rw.004 Tanah Baru, Beji, Depok City, West Java. The way to select partners is based on survey and interview results, namely that the majority of teenagers still often use slang and viral language that is not educational. The method of implementing this activity is education as well as direction and socialization. The results of this community service activity are Karang Taruna youth have gained knowledge and experience regarding polite and polite character through positive language attitudes so that it will really help teenagers in socializing with their surrounding environment.